Interactions and intersections of gendered bodies at work, at home and at play - Segal, Marcia Texler, 1940- (Advances in gender research, 2010)
The articles in the volume examine the intersection of gender with other characteristics in a variety of settings including factory floors and corporate offices, welfare offices, state legislatures, the armed forces, universities, social clubs and playing fields. Central themes running through several of the articles include how men and women conceive their identities and their futures and talk about and manage their work, family and leisure lives, how women view their bodies and images, and the progress women have -- or have not -- made in over-coming poverty and advancing in the corporate, legislative and military worlds. The research sites include Canada, Cuba, England, Greece, Israel, Mexico and the United States. As in previous volumes in the series, the authors employ a range of qualitative and quantitative methodologies and build on the current literature. Most of the articles have policy implications and are designed to stimulate further research. The volume is introduced with an essay by the editor and framed by an article about feminist intersectional research.